Detection of Exotoxin A gene in Pseudomonas aeruginosa from Clinical and Environmental samples - Al-Daraghi, Wathiq Abbas; Abdullah, Zaid Husamuldeen (Al-Nahrain Journal of Science, 2013)
PCR was used to detect Pseudomonas aeruginosa from clinical and environmental samples by amplifying a 396-bp region of the exotoxin A (ETA) structural gene sequence. Specific primer amplified ETA – positive P. aeruginosa DNA, whereas other species of Pseudomonas and GC-rich bacteria did not yield any 396-bp fragment. The specificity of the assay was 1% (just one isolate from 100 isolates used in this study(,this gene is not present in these isolates which means that these isolates do not have the ability to produce the Exo A toxin. With this PCR method, ETA – positive P. aeruginosa was detected only in one water sample in comparison with the use of the 16SrDNA gene which yielded 100% positive results of all tested isolates. This PCR method is rapid and more accurate than other diagnostic methods for the identification of P. aeruginosa strains, and it can be used to detect a low level of P. aeruginosa from different samples without using a selective medium or additional biochemical tests.